The Śāriputra and Raudrākṣa – On the Identity of the Bronze Drum in the Dunhuang Murals - Liao, Minqian (Távol-keleti Tanulmányok, 2025)
The story of Śāriputra and Raudrākṣa (Laoducha shengdou bian 勞度叉聖鬥變) involves Minister Sudatta’s encounter with the Buddha while seeking a bride for his son. Sudatta’s conversion leads to the construction of a monastery, sparking a contest between Buddhist monks and six sectarian teachers, with Śāriputra’s victory over Raudrākṣa showcasing Buddhist supremacy. The Dunhuang murals, based on the Xiangmo bianwen 降魔變文 (The Demon Conquering Story), are derived from the Buddhist Xian yu jing 賢愚經 (Sūtra of the Wise and the Foolish) and reflect a complex relationship between scripture, bianwen 變文, and the murals. This article explores how these forms differ while maintaining a connection, focusing on the dharma combat scenes and the symbolic use of dharma instruments. The cross-patterned jin drum (jin gu 金鼓) in the contest between Śāriputra and Raudrākṣa is a fascinating element embedded in the broader context of Dunhuang murals, manuscripts, and the religious and cultural symbolism of late Tang dynasty art. The article inquiry into the interpretation of the jin drum, its identity, and the significance of the cross pattern involves a detailed examination of archaeological, artistic, and textual evidence. The analysis of the Śāriputra and Raudrākṣa contest in Dunhuang murals and manuscripts, such as P.Tib.1293, reveals that the cross pattern on the jin drum holds deeper symbolic meaning beyond a ruptured drum skin. Traditionally, the cross pattern was thought to symbolise a ‘broken drum skin’ or ‘wind-broken drum’, representing the defeat of Raudrākṣa’s followers. However, this interpretation is challenged, suggesting that the pattern may have connections to the cultural and religious significance of bronze drums used by southern ethnic minorities in China. The cross-patterned drum is identified as a bronze drum, similar to the Chongyang 崇陽 bronze drum, and linked to the metal classification of ancient Chinese musical instruments. These drums were sacred objects used in rituals to communicate with deities, particularly among southern Chinese ethnic groups. The drum’s depiction in the contest scene reflects the clash between Buddhism and indigenous religious practices, symbolising the transition from animism and shamanism to Buddhist dominance. The broader cultural significance of this transformation highlights how Buddhism absorbed and transformed the religious symbols of local traditions, with the bronze drum serving as a metaphor for this shift. Ultimately, the jin drum in these murals represents not a rupture, but a deeper connection to the shamanistic traditions of the southern ethnic minorities and their gradual integration into Buddhist culture during the Tang dynasty.